Enterovirus circulation in the WHO European region, 2015–2022: a comparison of data from WHO's three core poliovirus surveillance systems and the European Non-Polio Enterovirus Network (ENPEN) - Harvala, Heli; Johannesen, Caroline K.; Benschop, Kimberley S.M.; Saxentoff, Eugene V.; Huseynov, Shahin; Hagan, José E.; Fischer, Thea K. (Elsevier BV, 2025)
Background: While the association of polioviruses with paralytic disease is well-documented and closely monitored via the Global Polio Eradication initiative, monitoring of the circulation and role of other non-polio enteroviruses in paralytic and non-paralytic disease has not received the same priority. We have assessed assess the role and potential effectiveness of the current enterovirus surveillance systems in the final stages of polio eradication.
Methods: We compared data on enterovirus circulation and clinical associations reported to the World Health Organization (WHO) Regional Office for Europe via the acute flaccid paralysis (AFP), clinical enterovirus, and environmental surveillance systems along with that collected by the European Non-Polio Enterovirus Network (ENPEN), 2015-2022.
Findings: This 8-year study analysed data from 63,659 samples from diagnosed enterovirus infections reported by 48 European countries, of which 27,699 were successfully typed (43.5%). This revealed the circulation of 67 individual enterovirus types primarily reported via ENPEN (85%; 19,712/23,220), whereas most poliovirus infections were reported via WHO (99.9%; 4484/4489). Only 20% of non-polio enterovirus positive AFP cases reported to WHO were successfully typed (105/544). Clinical data linked to these cases underscored the severity of paralytic non-polio enterovirus infections with 12 deaths compared to three deaths caused by poliovirus infections during the same study period.
Interpretation: The study documents non-polio enterovirus infections as a frequent cause of paralysis in Europe. Implementation of standardized monitoring and reporting of all enteroviruses identified from severely ill patients, including those with paralysis, would enhance our understanding of the burden of non-polio enterovirus infections without compromising poliovirus surveillance.